Correspondence Between the Johor Palace and Arab Merchants: A Historical Documentation Study in the 19th Century - Mohd Sohaimi Esa; Abang Mohd Razif Abang Muis; Wasino; Jalani Hamdan; Mohamad Shaukhi Mohd Radzi (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: Before the arrival of British colonial influence, Johor had developed close economic relations with Arab merchants who were active in sectors such as mining and agriculture. This article examines a series of royal correspondences (warkah) exchanged between the Johor royal court and Arab merchants, which serve as primary evidence of institutional trust and support in economic collaboration. Using the historical documentation method, the study explores both the textual content and the broader historical significance of these letters in the context of Johor’s economic expansion during the 19th century. Primary sources from archival records are analysed alongside secondary literature comprising scholarly works and previous studies. The findings highlight Johor’s open-door economic policy and the diplomatic role of the royal institution in fostering foreign investment, particularly from Arab entrepreneurs. By foregrounding royal correspondence as economic evidence, this study demonstrates how documentary heritage can revise prevailing colonial-era narratives that privilege a single entrepreneurial community, thus advancing Southeast Asian historiography on plural economic agency. It also underscores the policy relevance of archival preservation and digitisation, showing how improved access to warkah enables cross-disciplinary analysis of state-merchant relations and supports sustainable heritage governance. Abstrak: Sebelum datangnya pengaruh kolonial Inggris, Johor telah mengembangkan hubungan ekonomi yang erat dengan para pedagang Arab yang aktif di sektor-sektor seperti pertambangan dan pertanian. Artikel ini menelaah serangkaian korespondensi kerajaan (warkah) yang dipertukarkan antara istana kerajaan Johor dan pedagang Arab, yang menjadi bukti utama adanya kepercayaan institusional dan dukungan dalam kerja sama ekonomi. Dengan menggunakan metode dokumentasi sejarah, penelitian ini mengeksplorasi baik isi teks maupun signifikansi historis yang lebih luas dari surat-surat tersebut dalam konteks ekspansi ekonomi Johor pada abad ke-19. Sumber primer dari catatan arsip dianalisis bersama dengan literatur sekunder yang mencakup karya ilmiah dan penelitian sebelumnya. Temuan menunjukkan kebijakan ekonomi pintu terbuka Johor serta peran diplomatik lembaga kerajaan dalam mendorong investasi asing, khususnya dari pengusaha Arab. Dengan menempatkan korespondensi kerajaan sebagai bukti ekonomi, penelitian ini menunjukkan bagaimana warisan dokumenter dapat merevisi narasi era kolonial yang cenderung memusatkan perhatian pada satu komunitas wirausahawan saja, sehingga memperkaya historiografi Asia Tenggara tentang agensi ekonomi yang bersifat plural. Selain itu, penelitian ini juga menekankan relevansi kebijakan dalam pelestarian dan digitalisasi arsip, dengan menunjukkan bagaimana peningkatan akses terhadap warkah memungkinkan analisis lintas disiplin tentang hubungan negara-pedagang serta mendukung tata kelola warisan yang berkelanjutan.